Tweet tweet tick: a quantitative content analysis of risk communication about ticks on Twitter - Yang, Cheng-Xian; Baker, Lauri M.; McLeod-Morin, Ashley (Frontiers in Communication, 2024)
Introduction This study determined what information presented on Twitter (X) on tickborne diseases and their prevention and investigated the relationships between content information and engagement rate. The escalating incidence of vectorborne diseases, particularly those transmitted by ticks, has emerged as a significant public health concern. Communicating tick risks effectively to the public has become an urgent issue. Methods A quantitative content analysis was used to examine tick-related contents to understand how this infectious disease was framed on social media, with 340 tweets comprising the final sample for this study. Results In Twitter communication about tick risks, over half (55.3%) of the tweets lacked any visual content. Among the tweets with visuals, static photographs and illustrations/rendered images were the most commonly employed forms. Individual persons, news, and health/governmental organizations are the main tweeters. Additionally, most tweets use situational awareness, tool acquisition, and research frames and are in loss-frame. Approximately half (48.8%) of the tweets highlight adverse consequences or frame risk preparedness in negative terms. Tweets with visual aids have higher engagement rates, while those with URLs do not. Finally, tweets use different preparedness response frames and tend to use different gain-/ loss-frames. Specifically, tweets emphasizing situational awareness to alert the public about ticks and tickborne diseases predominantly utilize loss-frames, emphasizing higher risks than tool acquisition or research frames. Discussion The study’s findings underscore the importance of strategic communication in public health messaging on social media. By understanding the types of content that generate higher engagement and the framing that resonates with audiences, health organizations and other stakeholders can tailor their communications better to inform the public about tick risks and prevention strategies. This could lead to more effective disease prevention efforts and a better-informed public ready to take appropriate actions to protect themselves from tickborne diseases.